X-ray tomographic microscopy of Eocene coprolites from Pipestone Springs Main Pocket, southwest Montana - Jacquet, Sarah M.; Webb, Jeremy-Louis; Huntley, John Warren; Selly, Tara; Schiffbauer, James D. (Frontiers in Earth Science, 2023)
The Eocene Pipestone Springs Main Pocket (Renova Formation, Jefferson County, Montana, USA) is a locality renowned for its diverse Chadronian (late Eocene; ~38–33.9 million years ago) mammalian fauna and abundant coprolites. Two distinct coprolite size classes were previously identified in the trace fossil assemblage from which we selected representatives to investigate feeding behaviors and dietary selection of the producers. A subset of the selected coprolites was analyzed based on their compositional and taphonomic attributes using non-destructive x-ray tomographic microscopy in combination with more traditional methods including thin-section petrography, scanning electron microscopy, and energy dispersive spectroscopy. Among the features extracted in the tomographic data were skeletal fragments, including those showing evidence of bone-crushing; delicate hair molds; encrusted lithic fragments; and several irregular pores and cracks throughout the coprolites. Segmentation and volumetric renders permit quantitative assessment of the relative proportions of inclusions, revealing porosity as a primary volumetric element aside from the matrix and bone inclusions. There was no significant difference in the total volume of bone extracted between coprolite size class, though the smaller coprolites preserved a relatively higher volumetric proportion of undigested skeletal material. This multi-visualization approach provides a means to observe and evaluate differences in the coprolite gross morphology and inclusions across the two size classes, thereby offering valuable insights into the broader paleoecology of the Pipestone Springs Main Pocket coprolite producers and holding promise for comparable paleo-dietary studies of other coprolite-rich deposits.